Are there differences in the attention of elite football players concerning playing positions? - Moreira, L.; Malloy-Diniz, F. L.; Pinheiro, G. S.; Costa, V. T. (Science and Medicine in Football, 2022)
Purpose: This study aimed to compare the attention performance, by playing position, in elite Brazilian football players. Methods: A total of 66 professional players competing in the first division of the Brazilian Championship were evaluated. They were grouped according to their playing positions into 7 goalkeepers, 8 defenders, 15 fullbacks, 8 defensive midfielders, 13 attacking midfielders, and 15 forwards. The attention was evaluated using the QuotientTM ADHD System equipment. The group performances were compared using the Kruskal-Wallis Test and the post-hoc analysis using the Mann-Whitney Test. Results: Fullbacks showed less attentive behavior than defenders (U=9.000, p =0.001), defensive midfielders (U=12.500, p =0.002), offensive midfielders (U=48.000, p =0.007) and forwards (U=27.000, p =0.001). Fullbacks also had impulsive behavior longer than defenders (U=10.500, p =0.001) and defensive midfielders (U=12.000, p =0.002), as well as offensive midfielders had impulsive behavior longer than defenders (U=16.0000, p =0.004) and defensive midfielders (U=19.500, p =0.009). Conclusion: Players of defensive positions, as defenders and defensive midfielders, were more attentive and less impulsive than players of hybrid positions, responsible for both defensive and offensive actions, such as fullbacks and attacking midfielders. The present finding indicates that the defenders were the players who maintained the attention level for more time, while the fullbacks maintained for less time. Players in offensive playing positions (fullbacks and attacking midfielders) maintained their impulsive behavior for longer when compared to defensive positions (defenders and defensive midfielders).